Iron-Catalyzed Acceptorless Dehydrogenative Coupling of Alcohols With Aromatic Diamines: Selective Synthesis of 1,2-Disubstituted Benzimidazoles - Putta, Ramachandra Reddy; Chun, Simin; Lee, Seok Beom; Oh, Dong-Chan; Hong, Suckchang (Frontiers in Chemistry, 2020)
Benzimidazoles are important N-heteroaromatic compounds with various biological activities and pharmacological applications. Herein, we present the first iron-catalyzed selective synthesis of 1,2-disubstituted benzimidazoles via acceptorless dehydrogenative coupling of primary alcohols with aromatic diamines. The tricarbonyl (η4-cyclopentadienone) iron complex catalyzed dehydrogenative cyclization, releasing water and hydrogen gas as byproducts. The earth abundance and low toxicity of iron metal enable the provision of an ecofriendly and efficient catalytic method for the synthesis of benzimidazoles.